Economía de salud: importancia de su estudio - Quispe Sarmiento, Madian Esther (2021)
Health economics integrates economic, social, clinical, and epidemiological theories inorder to study the mechanisms and fac-tors that determine and condition theproduction, distribution, consumption, and financing of health services. For this reason,a review article was carried out in a bibliographic consultation in or-der to explain theneed for an economic approach in the health sector.